TEACHING ENGLISH FOR SPECIFIC PURPOSES (ESP) IN EFL CONTEXT - Raida Asfihana (English Department of Faculty of Tarbiyah and Teacher Training, 2013)
English for Specific Purposes (ESP) has been a current trend in language teaching for years. The ESP principles take part in the process of designing a syllabus or developing a teaching material for a particular course or study. Traditionally ESP courses were typically designed for intermediate or advanced adult learners. Nowadays many students can start to learn academic or vocational English at an earlier age and at a lower level of proficiency. A needs analysis, which is a part of ESP’s principles, is applied in order to find the needs of the course’s participants. This paper comprises three parts; the nature of ESP, the needs analysis in ESP, and ESP in EFL context.